Temporal reward discounting in children, adolescents, and emerging adults during an experiential task - Scheres, Anouk; Tontsch, Chandra; Thoeny, Allison L.; Sumiya, Motofumi (Frontiers in Psychology, 2014)
The goal of this study was to examine age effects on the ability/willingness to wait for large rewards in a real temporal reward discounting task from childhood to adulthood. Therefore, a real temporal discounting task was administered to children aged 6-12 (n=39), adolescents aged 13-17 (n=28), and young adults aged 18-19 (n=55). Findings indicated that the cross-sectional development of real temporal discounting followed a quadratic pattern across age groups, with adolescents choosing more often than children and adults to wait for the large delayed reward, resulting in reward-maximization. Various interpretations of this finding were offered, including a focus on reward maximization despite an immature ability to exert self-control, and flexible self-control which was high during this task as a result of strong motivation to maximize financial gains.